Lions of the West : heroes and villains of the westward expansion - Morgan, Robert, 1944- (Chapel Hill, N.C. : Algonquin Books of Chapel Hill, 2011)
Chronicles the lives of Americans who influenced the development of the Western frontier, including Thomas Jefferson, Kit Carson, and Sam Houston.
Brief chronology of the westward expansion era -- Presidents and vice-presidents before the Civil War -- Prologue : the empire for liberty -- Thomas Jefferson : he sees the elephant -- Andrew Jackson : Old Hickory at the Bend -- John Chapman : apples and angels -- David Crockett : comedian and martyr, his life and death -- Sam Houston : the president who loved to dance -- James K. Polk : Young Hickory keeps a diary -- Winfield Scott : Old Fuss and Feathers goes to the mountain -- Kit Carson : taking Boone's Trace to the Pacific -- Nicholas Trist : the search for a father voice -- Epilogue : John Quincy Adams : Old Man Eloquent.
"A Shannon Ravenel book."
Includes bibliographical references (p. 461-467) and index.
Keywords: Pioneers -- United States -- Biography; Pioneers -- West (U.S.) -- Biography; Presidents -- United States -- Biography; Frontier and pioneer life -- United States -- Biography; Frontier and pioneer life -- West (U.S.) -- Biography; Presidents -- United States -- Biography; United States -- Territorial expansion; West (U.S.) -- History -- To 1848.; United States -- Territorial expansion; West (U.S.) -- History